RISK FACTORS FOR IRON DEFICIENCY ANEMIA IN INFANTS AGED 6 MONTHS IN TEGAL REJO PUBLIC HEALTH CENTER, YOGYAKARTA, INDONESIA - Kusmiyati, Yuni; Tyastuti, Siti; Supriyati, Yulita Rizky; Sari, Nirmala (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Anemia is a global public health problem affecting both developing and developed countries with major consequences on human health as well as social and economic development. Anemia resulting from iron deficiency that may adversely affects the infants? cognitive and motor development. The objective of this research was to find out the risk factors of iron deficiency anemia (IDA) in 6 months old infants.Methods: This was an observational research with case-control design. Population was all 6 months old infants having been examined for their hemoglobin levels in Tegalrejo public health center in Yogyakarta from 2017 to 2018. 164 samples were taken with random sampling contained of 82 infants with anemia diagnosis in case group and 82 infants with normal hemoglobin levels for control group. Dependent variable was iron deficiency anemia (IDA) assessed based on hemoglobin level less than 11 gr% and independent variables were IDA risk factors (birth weight, sex, maternal education, maternal occupation, and maternal age) obtained from medical records and direct interviews. Data were analyzed by using logistic regression. Results: the risk factor influencing IDA was exclusive breastfeeding (p<0.05). Infants who did not receive exclusive breastfeeding had 2.16 folds higher risk of having IDA than those who received exclusive breastfeeding. Other risk factors such as birth weight, sex, maternal education, maternal occupation, and maternal age did not correlate significantly to iron deficiency anemia (IDA). Conclusion: Exclusive breastfeeding was the significant risk factor toward iron deficiency anemia in 6 months old infants after controlling other risk factors. Therefore, these finding can be implemented by maternal and child health practitioners to make iron deficiency anemia prevention program by eliminating or minimizing its risk factor.